O impacto da empregabilidade e qualidade de egressos do Curso Técnico em Mecânica do IFAM/CMC no Polo Industrial de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study aims to evaluate the employability and quality impact of former undergraduate students in the Mechanics Technical course at The Amazonas Federal Institute of Education, Science and Technology (IFAM) allocated in the Manaus Industrial Pole (PIM). It also focuses on the Institute historical performance and seeks to answer the following question: what is the employability and quality impact of the former undergraduate students in the Mechanics Technical Course allocated in the Manaus Industrial Pole? In order to meet these objectives, the research methodology was conducted in two stages. The first one, which covered bibliography and documents, sought reasons in many theorists who approached the subject and, in addition, IFAM departments in Manaus Downtown Campus (CMC) which held information about the courses offered were consulted. In the second stage, technical questionnaires were applied. They contained 24 (twenty- four) closed questions and 2 (two) open questions, delimiting the 2009, 2010 and 2011 conclusive students. The course modalities chosen were Integrated Study, Subsequent Study and PROEJA (Young and Adults Education). This work fits Case Study methodology with explanatory and Descriptive Research. The results showed that from the 135 undergraduate students who undergone the research, 80% have found activity in the labor market, 75.56% are employed and 20% are unemployed. Among the unemployed, 15.5% are pursuing higher education in their training area and 4.44% are effectively without occupation. From the employed population, 85.30% are allocated at PIM, which corresponds to 5.8 times the total number of the employed undergraduates in other types of enterprises. In addition, 100% of former undergraduates working now at PIM are working in the same academic area they had studied at IFAM/CMC. In general, the requirements that address the students’ skills performance were well evaluated. This result reveals that, despite some inconsistencies, the employability level of these professionals at PIM is impacting, both in quantity and quality terms, making it possible to respond positively to the research question.
Keywords: Técnico em Mecânica; Polo Industrial de Manaus (PIM); Empregabilidade; Ensino técnico; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO